2014
DOI: 10.1159/000356806
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidative-Antioxidative Balance of Cells in Different Types of Renal Replacement Therapy

Abstract: Background: Patients suffering from chronic kidney disease (CKD) are exposed to increased oxidative stress and disturbances manifesting in the enzymatic and non-enzymatic antioxidative defence system. The object of the research was to assess the differences between conservative treatment, peritoneal dialysis and haemodialysis in moderating cellular antioxidative agents. Methods: The group examined comprised 145 patients. The activities of superoxide dismutase, catalase, glutathione peroxidase, glutathione redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
3
18
0
Order By: Relevance
“…Interestingly, our results showed an increase in plasma SOD levels 1 hour after initiating the dialysis session. Varan et al [5] and Stępniewska et al [28] found the same results at the end of the dialysis session. This increase may be explained by a compensatory mechanism that mobilizes the antioxidant defense system and prevents the free radicals produced during the dialysis session.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, our results showed an increase in plasma SOD levels 1 hour after initiating the dialysis session. Varan et al [5] and Stępniewska et al [28] found the same results at the end of the dialysis session. This increase may be explained by a compensatory mechanism that mobilizes the antioxidant defense system and prevents the free radicals produced during the dialysis session.…”
Section: Discussionmentioning
confidence: 55%
“…Importantly, CKD affects red blood cell and platelets that are activated and produce reactive oxygen species, which in turn activates intracellular redox enzymes, for example, superoxide dismutase, catalase, glutathione peroxidase, transferases, and glutathione reductase [6], showing and increased redox imbalance in platelets and red blood cells of CKD patients [5,6,[18][19][20][21]. Markers of protein and lipid peroxidation, for example, malondialdehyde (MDA/TBARS), advanced glycation end products including pentosidine [7,8], advanced oxidation protein products [1,5] are also altered in CKD; however, to date, there are no redox markers that are readily used in the point-of-care testing.…”
Section: Discussionmentioning
confidence: 99%
“…Iron therapy, especially intravenous iron, has been found to increase free ion and induce the peroxidation of lipid and protein, aggravate the microinflammation, and result in increased SOD and CRP ( 17 20 ). SOD, as an antioxidant enzyme representative, can remove oxygen-free radicals and block the damage caused by free radicals, thereby reflecting the level of oxidative stress ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%